The Role of Young People's Political Participation in Building a Strong Democracy: Case Study in Indonesia - Kalfin; Siti HadiatY Yuningsih; Chun Wang (International Journal of Humanities, Law, and Politics, 2023)
This research discusses political participation among young people as the key to building and improving the political system in Indonesia. Young people play an important role as the future generation of voters who have great potential in determining political direction and policies. In this context, political awareness and political education are key factors in forming a young generation who are active and responsible in the political process. This research also discusses challenges such as apathy towards politics and efforts that can be made to overcome this problem. Through active participation, comprehensive political education, and involvement in political dialogue, the younger generation has great potential to become agents of positive change in building a strong and clean democracy in Indonesia.